FINNISH PRIMARY AND PRESCHOOL TEACHERS REFLECTING ON GENERIC SKILLS: HELSINKI UNIVERSITY GRADUATES’ PERCEPTIONS - Ruokonen, Inkeri Maria; Sepp, Anu (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Lately there has been much interest in how university level studies develop students’ generic skills and to what extent university education meets the requirements of working life. Generic skills are needed in every profession and field. The term has been widely used during the past few decades due to the rapid change in society and working life. In order to develop teacher education in Finland, several research projects have been launched. The aim of this research was to find out preschool and primary school teachers’ perceptions to what extent and what kind of generic skills their teacher’s pedagogical studies had supported most. The data used in this study was collected electronically by E-lomake that was distributed through different social media channels. The received answers of induction phase teachers (n = 23) were analyzed both qualitatively and quantitatively. To gain a better insight, two of the respondents were also interviewed and the answers analysed qualitatively.The results revealed that in general the respondents found that the attained generic skills helped them to cope with working life. Communication in a foreign language, acting in a multicultural environment, digital and communicative skills, and coping with stress were mentioned as not relevant or needing more attention.